Pengembangan Desa Kanoman Berbasis Potensi Virgin Cocount Oil - Mayasari, Agatha (Jurnal Atma Inovasia, 2023)
The implementation of the Real Work Lecture (KKN) held by Atma Jaya University Yogyakarta is carried out online. This is due to a pandemic caused by the SARS-CoV2 virus, where everyone is asked to carry out their activities from home because the SARS-CoV2 virus will spread more quickly when in a crowd. The purpose of this KKN activity is to develop the social spirit and dedication of students and students to the community. Students and college students are expected to be able to increase empathy and concern. In addition, KKN is a form of university involvement in the development of an area from various sectors, especially in Kanoman Village, Panjatan, Kulon Progo Regency, Special Region of Yogyakarta. Data was collected using literature study techniques which will be analyzed further. Group 95 has a work program in the form of E-books and Videos regarding the development of the potential of Kanoman village, namely coconut into Virgin Cocount Oil, with the hope that Kanoman village can become a developed, prosperous and prosperous village.